2023
DOI: 10.1111/conl.12994
|View full text |Cite
|
Sign up to set email alerts
|

Testing a conservation compromise: No evidence that public wolf hunting in Slovakia reduced livestock losses

Miroslav Kutal,
Martin Duľa,
Alisa Royer Selivanova
et al.

Abstract: Variation in the legal status and management of wolves (Canis lupus) across EU Member States provides a good opportunity to test the effectiveness of different practices to reduce livestock losses. This opportunity for testing is particularly useful for lethal interventions, as they are among the most controversial actions within the large carnivore management toolbox. We aimed to test a conservation compromise adopted in Slovakia, based on a public wolf‐hunting scheme and annual hunting quotas between 2014 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Five of the seven comparative studies on social canids showed that lethal control significantly decreased damage recurrence, whereas Santiago-Avila et al (2018) and Kutal et al (2023) found no significant effect of lethal control on damages. Yet, results suggested variability in the efficiency of lethal control.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Five of the seven comparative studies on social canids showed that lethal control significantly decreased damage recurrence, whereas Santiago-Avila et al (2018) and Kutal et al (2023) found no significant effect of lethal control on damages. Yet, results suggested variability in the efficiency of lethal control.…”
Section: Introductionmentioning
confidence: 99%
“…damages from compensation schemes). Most of retrospective studies on social canids (gray wolves Canis lupus, dingoes Dingo dingo, coyotes Canis latrans) were correlative and tested for a relationship between the number of livestock damages and the number of killed predators (Šuba et al, 2023;Fernández-Gil et al, 2016;DeCesare et al, 2018;Conner et al, 1998;Allen, 2015;Kutal et al, 2023). However, this approach is not suited to infer causality and is subject to high risks of confounding factors and to analytical variability (Gould et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations